2016
DOI: 10.18632/oncotarget.11329
|View full text |Cite
|
Sign up to set email alerts
|

Construction and immunological characterization of CD40L or GM-CSF incorporated Hantaan virus like particle

Abstract: Infection of Hantaan virus (HTNV) usually causes hemorrhagic fever with renal syndrome (HFRS). China has the worst epidemic incidence of HFRS as well as high fatality. Inactivated whole virus has been used for HFRS vaccination, however there are still problems such as safety concerns. CD40 ligand (CD40L) and granulocyte macrophage colony-stimulating factor (GM-CSF) are well-known immune stimulating molecules that can enhance antigen presenting, lymphocytes activation and maturation, incorporation of CD40L and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…Virus isolation was performed according to previously published methods (Ying et al, 2016; Mingxiao et al, 2011; Jakubowska et al, 2016) Briefly, 50–60 adult bees were completely homogenized with a mortar and pestle in 10 mL of phosphate-buffered saline (pH 7.4), containing 0.5% nonylphenol ethoxylate, then the homogenate was incubated for 30 min at 20 °C. After this, the homogenate was centrifuged at 5,000× g for 20 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Virus isolation was performed according to previously published methods (Ying et al, 2016; Mingxiao et al, 2011; Jakubowska et al, 2016) Briefly, 50–60 adult bees were completely homogenized with a mortar and pestle in 10 mL of phosphate-buffered saline (pH 7.4), containing 0.5% nonylphenol ethoxylate, then the homogenate was incubated for 30 min at 20 °C. After this, the homogenate was centrifuged at 5,000× g for 20 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…How to improve the immunogenicity of VLPs is very important. It was reported that either CD40L-or GM-CSF-contained HTNV VLP expression in sf9 insect cells or CHO cells (Ying et al, 2016) could enhance the activation of macrophages and dendritic cells. CD40L/GM-CSF incorporation into VLPs induced elevated levels of HTNV-specific antibodies and neutralizing antibodies in mice.…”
Section: Vlp Vaccinesmentioning
confidence: 99%
“…In China, HTNV virus-like particles (VLPs) decorated with CD40L or GM-CSF had been constructed using the HTNV M segment and CD40L/GM-CSF gene, co-transfected with a vector containing S segment into dihydrofolate reductase Chinese hamster ovary cells (dhfr-CHO). CD40L or GM-CSF-anchored HTNV VLP showed enhanced activation of macrophages and dendritic cells in vitro [ 53 , 54 ]. These HTNV VLPs have provided stable, long-term protection with a high titer of neutralizing antibody in mice 6 months after immunization and HTNV-specific cellular immune responses via higher expression of IFN-g and CTL responses [ 54 ].…”
Section: Preventionmentioning
confidence: 99%
“…These HTNV VLPs have provided stable, long-term protection with a high titer of neutralizing antibody in mice 6 months after immunization and HTNV-specific cellular immune responses via higher expression of IFN-g and CTL responses [ 54 ]. CD40L or GM-CSF decorated VLPS induced humoral and cellular immunity were greater than undecorated VLPs or inactivated HTNV vaccines in mice [ 53 , 54 ].…”
Section: Preventionmentioning
confidence: 99%